Meanings and experiences Of patients living with psoriasis (Research, Society and Development, 2021)
Objective: The objective was to understand the meaning of the experiences of patients living with psoriasis. A qualitative research was carried out using an unstructured script. Patients diagnosed with psoriasis registered and followed at the dermatology outpatient clinic of a Polyclinic of the Unified Health System in a municipality located in the north of Minas Gerais participated in the research. The answers obtained were grouped in order to meet the objectives and categorized to enable the discussion using the collective subject's discourse technique. The results revealed that in addition to the clinical characteristics of psoriasis, psychological conditions and satisfaction with physical appearance are factors that interfere in the impact of the disease on quality of life. These data point to the clinical peculiarities of the disease and psychological functioning, influencing psychosocial adaptation to patients with psoriasis. It is expected that this research can contribute to the aspects and changes in the lives of people with the disease, making society and the family aware of the importance of welcoming, caring for and respecting the individual.